2020
DOI: 10.1155/2020/8873663
|View full text |Cite
|
Sign up to set email alerts
|

External Iliac Artery Injury and Thrombosis during Laparoscopic Gynecologic Surgery

Abstract: Although vascular injury during laparoscopic surgery is rare, it is occasionally reported. Previously, several physicians have reported cases of compartment syndrome resulting from a thrombus during gynecologic surgery. However, few reports describe thrombosis occurring in artery vessels as a result of applying angiopressure. Herein, we report the case of a 53-year-old woman with endometrioid carcinoma and a vascular injury that resulted in thrombus formation; this is the first such case to be reported. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Risk factors discussed in the literature include but are not limited to atherosclerotic disease, embolism from the heart, prolonged surgical positioning and trendelenburg, intravascular dehydration, hyper-coagulopathy, dissection, and vascular trauma 13 . In the medical literature, 9 case reports have previously described pelvic surgeries complicated by acute limb ischemia, 6 of which were in the setting of gynecologic malignancies ( Sahara et al, 2019 , Yeon et al, 2017 , Nakamura et al, 2008 , Ishikawa et al, 2020 , Hamilton and Robinson, 1996 ); ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk factors discussed in the literature include but are not limited to atherosclerotic disease, embolism from the heart, prolonged surgical positioning and trendelenburg, intravascular dehydration, hyper-coagulopathy, dissection, and vascular trauma 13 . In the medical literature, 9 case reports have previously described pelvic surgeries complicated by acute limb ischemia, 6 of which were in the setting of gynecologic malignancies ( Sahara et al, 2019 , Yeon et al, 2017 , Nakamura et al, 2008 , Ishikawa et al, 2020 , Hamilton and Robinson, 1996 ); ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative arterial thrombi are exceedingly rare after laparoscopic surgery and are only noted in scant case reports, mainly in patients with preexisting hematologic disorders, severe arteriosclerotic disease, or prior radiation therapy. Specifically in patients with gynecological cancer, there are less than 10 reported cases of acute postoperative arterial thromboembolic events in the current literature ( Levenback et al, 1996 , Nakamura et al, 2008 , Ishikawa et al, 2020 , Hamilton and Robinson, 1996 ) ( Table 1 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gyimadu et al concluded that the occurrence of vascular injuries during the course of PLNDGO may be due to variations in the anatomy of great retroperitoneal vessels. In medical literature the frequency of such abnormalities varies between 5.6 and 23.0% [ 64 , 65 , 66 , 67 , 68 ].…”
Section: Uterine and Obturator Artery Variations Related To Plndgmentioning
confidence: 99%